2017
DOI: 10.1364/oe.25.010345
|View full text |Cite
|
Sign up to set email alerts
|

Depth-dependent dispersion compensation for full-depth OCT image

Abstract: A depth-dependent dispersion compensation algorithm for enhancing the image quality of the Fourier-domain optical coherence tomography (OCT) is presented. The dispersion related with depth in the sample is considered. Using the iterative method, an analytical formula for compensating the depth-dependent dispersion in the sample is obtained. We apply depth-dependent dispersion compensation algorithm to process the phantom images and in vivo images. Using sharpness metric based on variation coefficient to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…68,71 This is achieved by multiplying the spectral data (which is formerly linearized in k-space, zero-padded to 2 12 pixels and spectrally shaped) with a compensating phase term e −iφðkÞ . 69,72 The empirically determined phase correction amounts to E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 0 1 ; 3 2 6 ; 7 5 2…”
Section: Eoct Scanner Performancementioning
confidence: 99%
“…68,71 This is achieved by multiplying the spectral data (which is formerly linearized in k-space, zero-padded to 2 12 pixels and spectrally shaped) with a compensating phase term e −iφðkÞ . 69,72 The empirically determined phase correction amounts to E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 0 1 ; 3 2 6 ; 7 5 2…”
Section: Eoct Scanner Performancementioning
confidence: 99%
“…Unfortunately, the broader the spectral range is, the more prominent chromatic dispersion effects become. Whereas it is fairly easy to compensate the dispersion mismatch in the arms of an interferometer 2 8 , the resolution degradation for deeper layers of an object caused by a dispersive character of these layers is challenging to mitigate as it requires the information about the dispersion coefficients of each layer 9 . It was shown that the practical limit for axial resolution—one which weighs in the bandwidth-dispersion trade-off during imaging of bulk objects such as the eye—is 1 μm 10 and this limit has already been achieved in OCT in both visible 11 13 and NIR 14 , 15 wavelength ranges.…”
Section: Introductionmentioning
confidence: 99%
“…However, only half of the available depth range can be used for imaging in standard SD-OCT systems, otherwise complex conjugate mirror items overlap with sample structures. To overcome this problem, several full-range techniques have been proposed, which follow two categories: phase modulation methods [3][4][5] and dispersion-coded methods [6][7][8].…”
Section: Introductionmentioning
confidence: 99%